Return migration, investment in children, and intergenerational mobility: comparing sons of foreign and native born fathers - Christian Dustmann (Institute for the Study of Labor (IZA), 2007)
This paper studies parental investment in education and intergenerational earnings mobility for father-son pairs with native and foreign born fathers. We illustrate within a simple model that for immigrants, investment in their children is related to their return migration probability. In our empirical analysis, we include a measure for return probabilities, based on repeated information about migrants' return intentions. Our results suggest that educational investments in the son are positively associated with a higher probability of a permanent migration of the father. We also find that the son's permanent wages are positively associated with the probability of the father's permanent migration.
Keywords: 300; Intergenerational mobility; return intentions; educational investment; earnings; Migranten; Kinderbetreuung; Bildungsinvestition; Rückwanderung; Generationenbeziehungen; Soziale Mobilität; Deutschland